POLA PENGELUARAN DAN KONSUMSI MAHASISWA PERANTAUAN FAKULTAS PERTANIAN UNIVERSITAS LAMPUNG - Atikah Khansa, Shafrina; Indriani, Yaktiworo; Adawiyah, Rabiatul (Lampung University, 2025)
This study aims to determine expenditure and consumption patterns of students living away from home at the Faculty of Agriculture (FP), University of Lampung (Unila) at by a survey method. The research samples consisted of 80 respondents, who were students of the Department of Agribusiness and Agricultural Product Technology. The data collection was conducted in April-May 2024 and analyzed by quantitative and descriptive methods. The results showed that the average of students living away from home total expenditure was Rp1,270,348.00 per month consisted of food expenditure as Rp684,848.00 per month (53.91%) and non-food expenditure as Rp585,500.00 per month (46.09%). The average of Desireable Dietary Pattern (DDP) score of the students living away from home was 52.88, in which the DDP score of female was 53.35, higher than that of male, which was 51.38. The types of food most frequently consumed by students were rice, fried chicken, oil, chicken eggs, and chili sauce. The average energy and protein intake of FP Unila students living away from home was 1,639.4 kcal and 67.8 g, respectively.